TIME IS MONEY: BENJAMIN FRANKLIN AND THE VEXING PROBLEM OF PROVERB ORIGINS - Villers, Damien; Mieder, Wolfgang (Proverbium - Yearbook, 2017)
This article is an investigation of the origins and the dissemination of Time is money, which is commonly but erroneously attributed to Benjamin Franklin. Online tools and corpora are used to uncover the British origins of the proverb, as well as possible models for its coin-age. The combination of concordance tools and a theoretical framework for “proverb genesis” allows for discoveries on the stages of its birth, as well as on their chronology. Special attention is paid to the role Franklin played in the propagation of the proverb, and therefore its American birth.